196k views
3 votes
Need help bad !!!!!!!!!!!!​

Need help bad !!!!!!!!!!!!​-example-1
User LampShaded
by
5.5k points

2 Answers

3 votes

Answer:

B

Explanation:

Using the midpoint formula

midpoint = [
(1)/(2)(
x_(1) +
x_(2)),
(1)/(2)(
y_(1) +
y_(2)) ]

with (x₁, y₁ ) = (- 2, 4) and (x₂, y₂ ) = (6, - 4)

midpoint = [
(1)/(2)(- 2 + 6),
(1)/(2)(4 - 4) ]

= (2, 0) → B

User Krulik
by
6.3k points
4 votes
there are 2 order pairs there (6,-4),(-2,4)
find the midpoint using the formula

(x1+x2)/2 , (y1+y2)/2
x=6 and -2
y=-4 and 4

(6+2)/2 , (-4+4)/2
8/2 ,0/2
the midpoint is (4,0) A
Need help bad !!!!!!!!!!!!​-example-1
User Le Minaw
by
4.3k points